Survey on UASN topology control - Hong-ri LIU; Yun-xiao SUN; Jia SONG; Yang LIU; Jun-heng HUANG; Bai-ling WANG (网络与信息安全学报)
Firstly,the status of current research of water acoustic sensor network nodes and communication structure were summed up,and the impact of the time synchronization,MAC protocol and deployment strategies on network topology control were analyzed.Secondly,following successive process of network deployment,three scientific issues including the deployment generation of topological structure,the dynamic evolution of topology and healing mechanism of topology were extracted.Finally,a new thought for future research was provided.